A DPA-resistant crypto engine for UHF RFID tag. (2015) - Zhu, Linghao; Wu, Cheng; Wu, Linyin; Wang, Junyu; Min, Hao
Differential power analysis (DPA) is a potential threat to the security of radio frequency identification (RFID) system. In this paper, the hardware implementation of a DPA-resistant crypto engine for RFID tag conforming to ISO/IEC 18000-63 protocol is presented. The masking scheme is adopted in the AES crypto engine to protect the tag from DPA attacks. The design is implemented using 0.13 µm CMOS technology. According to simulation results, the DPA-resistant crypto engine occupies 38% more area and consumes 20% more power than the unmasked one. The area of the whole tag baseband including the DPA-resistant crypto engine is about 163, 000 µm². The average power consumption during a query round is 21.2 µW under 1 V voltage and 1.28 MHz clock frequency.